"What a Waste. Beautiful, Sexy Gal. Hell of a Lawyer.": Film and the Female Attorney - Miller, Carolyn Lisa (Columbia Journal of Gender and Law, 1994)
This Article, through its analysis of films which feature female attorneys, brings both the pleasure of film and the pleasure of resistance to the project of envisioning a world in which female attorneys can succeed, both in fantasy and in reality.